Zika-related adverse outcomes in a cohort of pregnant women with rash in Pernambuco, Brazil. - Ricardo Arraes de Alencar Ximenes; Demócrito de Barros Miranda-Filho; Ulisses Ramos Montarroyos; Celina Maria Turchi Martelli; Thalia Velho Barreto de Araújo; Elizabeth Brickley; Maria de Fátima Pessoa Militão de Albuquerque; Wayner Vieira Souza; Liana O Ventura; Camila V Ventura; Adriana L Gois; Mariana C Leal; et al. (PLoS Neglected Tropical Diseases)
Background While Zika virus (ZIKV) is now widely recognized as a teratogen, the frequency and full spectrum of adverse outcomes of congenital ZIKV infection remains incompletely understood. Methods Participants in the MERG cohort of pregnant women with rash, recruited from the surveillance system from December/2015-June/2017. Exposure definition was based on a combination of longitudinal data from molecular, serologic (IgM and IgG3) and plaque reduction neutralization tests for ZIKV. Children were evaluated by a team of clinical specialists and by transfontanelle ultrasound and were classified as having microcephaly and/or other signs/symptoms consistent with congenital Zika syndrome (CZS). Risks of adverse outcomes were quantified according to the relative evidence of a ZIKV infection in pregnancy. Findings 376 women had confirmed and suspected exposure to ZIKV. Among evaluable children born to these mothers, 20% presented with an adverse outcome compatible with exposure to ZIKV during pregnancy. The absolute risk of microcephaly was 2.9% (11/376), of calcifications and/or ventriculomegaly was 7.2% (13/180), of additional neurologic alterations was 5.3% (13/245), of ophthalmologic abnormalities was 7% (15/214), and of dysphagia was 1.8% (4/226). Less than 1% of the children experienced abnormalities across all of the domains simultaneously. Interpretation: Although approximately one-fifth of children with confirmed and suspected exposure to ZIKV in pregnancy presented with at least one abnormality compatible with CZS, the manifestations presented more frequently in isolation than in combination. Due to the rare nature of some outcomes and the possibility of later manifestations, large scale individual participant data meta-analysis and the long-term evaluation of children are imperative to identify the full spectrum of this syndrome and to plan actions to reduce damages.